New Trends in Anterior Cruciate Ligament Reconstruction: A Systematic Review of National Surveys of the Last 5 Years - Grassi, Alberto (Joints, 2018)
The purpose of this study was to analyze national surveys of orthopaedic surgeons on anterior cruciate ligament (ACL) reconstruction to determine their preferences related to the preferred graft, femoral tunnel positioning, fixation and tensioning methods, antibiotic and anti-thromboembolic prophylaxis, and use of tourniquet and drains. A systematic search of PubMed, Web of Science, and Cochrane Library was performed. Inclusion criteria were surveys of ACL reconstruction trends and preferences published in the past 5 years (2011–2016), involving members of national societies of orthopaedics. Information regarding survey modalities, population surveyed, graft choice both in the general or in the athletic population, surgical technique, fixation, use of antibiotic, tourniquet, drains, and anti-thromboembolic prophylaxis was extracted. Eight national surveys were included from Europe (three), North or Latin America (three), and Asia (two). Overall, 7,420 questionnaires were sent, and 1,495 participants completed the survey (response rate ranging from 16 to 76.6%). All surveys reported the hamstring tendon (HT) autograft as the preferred graft, ranging from 45 to 89% of the surveyed population, followed by bone-patellar tendon-bone (BPTB) graft (2–41%) and allograft (2–17%). Only two surveys focusing on graft choice in athletic population underlined how in high-demand sportive population the graft choices changes in favor of BPTB. Single-bundle reconstruction was the preferred surgical technique in the four surveys that investigated this issue. Five surveys were in favor of anteromedial (AM) portal and two in favor of trans-tibial technique. Suspension devices for femoral fixation were the preferred choice in all but one survey, while interference screws were the preferred method for tibial fixation. The two surveys that investigated graft tensioning were in favor of manual tensioning. The use of tourniquet, antibiotics, drains, and anti-thromboembolic prophylaxis were vaguely reported. A trend toward the preference of HT autograft was registered in all the surveys; however, sport participation has been highlighted as an important variable for increased use of BPTB. Single-bundle reconstruction with AM portal technique and suspension femoral fixation and screws fixation for the tibia seem the preferred solution. Other variables such as tensioning, antibiotic, anti-thromboembolic prophylaxis, tourniquet use, and drains were investigated scarcely among the surveys; therefore, no clear trends could be delineated. This is a Level V, systematic review of expert opinion study.